DUKUNGAN SOSIAL DALAM PENGATURAN GAYA HIDUP SEHAT PENDERITA HIPERTENSI - Loriza Sativa Yan; Nur Insani (Jurnal Endurance, 2023)
Establishing a healthy lifestyle is a big challenge for people with hypertension. For this reason, it is necessary to provide social support so that people with hypertension can improve their health behaviour. This study aims to provide an overview of social support in healthy living settings for people with hypertension. The design of this study uses a cross-sectional design. The study involved 147 hypertensive patients aged over 18 years who were selected by random sampling technique. The results of the study described that most of hypertension sufferers are late adults, live with extended families, and social support comes from peers. Hypertension sufferers have received support in the form of care assistance and motivation during regular healthy living arrangements. What is recommended is to increase social support sources and control arrangements for a healthy lifestyle in implementing daily activities. Keywords: Social support, Hypertension, Healthy lifestyle